Effect of Additioning Microencapsule Product of Noni Fruit Extract (Morinda citrifolia Linn.) as Feed Additive on Slaughter Weight, Edible Weight and Inedible Weight of Sentul Chicken - Rachmanita, Meita Putri; Widjastuti, Tuti; Dudi, Dudi (Jurnal Produksi Ternak Terapan, 2025)
Sentul chicken is a native Indonesian chicken breed originating from the Ciamis Regency area that has the potential to be an egg and meat producer. Utilization of bioactive compounds contained in noni fruit is expected to increase the weight produced through increased absorption of feedstuff nutrients. This study involved 100 Sentul chickens divided into four treatment groups with five repetitions, using a variety of feed containing microencapsules at doses of 0, 75, 150, and 225 mg/kg MNFE. The microencapsulation method in this study used maltodextrin as the coating and spray drying as the drying method. The research findings indicated that the use of microencapsulated noni fruit extract significantly affected the slaughter weight and edible weight. The most effective dose was found at 75 mg/kg MNFE, which resulted in an optimal increase in slaughter weight and edible weight but did not reduce inedible weight. Therefore, the use of microencapsulated noni fruit extract not only contributes to the increase in weight, but also has the potential to become an alternative natural feed additive in the livestock industry, especially in an effort to reduce dependence on Antibiotic Growth Promoter (AGP).